The impact of rurality on anxiety in secondary school students: a systematic review. Issue 4 (3rd July 2020) - Harvey, Kathryn; Clark, Jane
ABSTRACT: Anxiety is an identified risk for students and its rates are increasing amongst young people. While there are numerous articles available on anxiety and adolescents, little is known about the impact that rurality may have on anxiety in secondary school students. In light of this, a systematic literature review was undertaken to explore not only the ways in which anxiety impacts upon students in secondary school but also whether living and studying in a rural context presented additional stressors. Through an examination of 29 peer-reviewed publications, six key themes were identified relating to the area under investigation: anxiety, long-term effect of anxiety, school completion, academic achievement, rurality and educational interventions. The conclusion of this review is that while rurality can have a significant negative impact upon students' anxiety and its management, through the implementation of school-based interventions, teachers can minimise its effect on academic outcomes.